Ion Imprinted Affinity Cryogels for the Selective Adsorption Uranium in Real Samples - İbrahim Dolak (Iranian Journal of Chemistry & Chemical Engineering, 2019)
In this research, selective adsorption of U(VI) in aqueous solutionsin the presence of various lanthanide ions by using U(VI)-imprinted cryogel polymer was conducted. For this purpose, the prepared pHEMA-(MAH)3-U(VI) cryogel polymer by free radical polymerization method. U(VI) was desorbed with 5.0 mol/L HNO3 and thus U(VI)-imprinted were created onto p-HEMA-(MAH)3 cryogel polymer. To determine the optimum conditions, in the process of selective adsorption of U(VI) ion to U(VI)-imprinted p-HEMA-(MAH)3 cryogel polymer, some parameters such as pH, flow rate, initial U(VI) concentration were investigated. Under the optimum conditions, the maximum adsorption capacity was obtained as 74.80 mg/g. Selectivity studies were also carried out in the presence of Nd(III), La(III) and Y(III) ions using U(VI)-imprinted p-HEMA-(MAH)3 cryogel polymer. The obtained adsorption order under competitive conditions was U(VI) ˃ La(III) ˃Y(III) ˃Nd(III).